The Relationships Between Destination Image, Tourist Interest in Travelling and Promotion: The Case of Bedengan, Malang, Indonesia - Hidayatullah, Syarif; Sutikno, Sutikno; Alvianna, Stella; Rachmawati, Ike Kusdyah (UUM Press, 2021)
The existence of tourist objects and attractions is the most important component in a tourism activity. Likewise with the existence of tourist attractions in Bedengan, Malang, Indonesia, the number of existing visits has fluctuated. This is because there are several interesting factors encouraging tourists to visit Bedengan such as, its location which is close to several campuses, its large area which makes it suitable to set up a camp, landmass that can be used for outdoor, a very serene view with a narrow river and clean and fresh water from a waterfall, and its cheap price for the entrance ticket which is only Rp 5,000. This study discusses the image of Bedengan as tourist destination and its influence on tourist interest in travelling, through promotion as a mediating variable. Four hypotheses were developed in order to answer the objective of the study. The population in this study were tourists who visited Malang Bedengan Nature Tourism, with a sample of 100 respondents. The analysis technique used is multiple linear regression with two models. The tested hypotheses are concluded as: 1) There is a positive and significant effect of destination image on tourist interest in travelling, 2) There is a positive and significant influence of promotion on tourist interest in travelling, 3) There is a positive and significant influence of destination image on promotion, and 4) There is a positive and significant effect of destination image on tourist interest in travelling through promotion. The findings of the study can assist the stakeholders to use promotional tools to market the image of Bedengan as tourist destination.